The effect of blood lead level on packed cell volume in a sample of Iraqi population. - Sudek, Hanan L.; Jaffar, Israa F. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Low hemoglobin levels and lead exposure remain significant health issues in many parts of the world, often occurring together, however most of the researches concentrate on the effect of high levels of lead .This study aimed to demonstrate the effect of blood lead level on hemoglobin and packed cell volume (PCV).Patients and Methods: Fifty eight adult volunteers were enrolled in this study with age range between 23 and 55 years, working in the different departments in medical college of Baghdad University. Whole blood was withdrawn in EDTA tubes. Hemoglobin and PCV were measured and blood lead level was estimated using blood lead testing system including lead care kit and lead care analyzer.Results: After measuring blood lead level and correlate it to PCV in all volunteers results revealed a significant negative correlation between them which is obvious in both smokers and non-smokers groups. Age was found to correlate positively and significantly with blood lead level in non smokers group. Comparing the blood levels of lead and PCV in both smokers and non-smokers shows non-significant difference between them although blood lead level was higher in smokers group.Conclusion: Blood lead levels is increased with age. There is a significant decrease in PCV with the increase in blood lead level which is noticed in both smokers and non smokers. There is a significant increase of blood lead levels in smokers group.